Analyzing the Foundations of Dialogical Principle in Narrative and Illustration of the Tale of Ebony Horse in One Thousand and One Night Manuscript - Sedigheh Edraki; Hossein Abeddoost; Ziba Kazempoor (مجله مطالعات ایرانی, 2023)
Introduction The tale of ebony horse is one of the illustrations of the One Thousand and One Night collection, enjoying considerable substantive and pictorial value. This work was illustrated during the Qajar era and is currently preserved in the Golestan palace complex. The present research aims to analyze dialogism and polyphony, the space-time continuum, the relationship between the self and otherness, and carnivalism in the text and illustrations of the ebony horse tale from the One Thousand and One Night manuscript. This analysis seeks to shed some light on how one can identify the foundations of the theory of dialogical principle in the content of the ebony horse tale and its illustrations. It also takes stock of similarities and differences of dialogism in the story narrative and images of this version. Methodology The research method is descriptive-analytical, and the method of collecting library information is through note-taking and image reading. The analysis method is qualitative. The research community includes the textual and pictorial materials of the 12th and 13th centuries in the Qajar era, especially the illustrations of the One Thousand and One Nights by Sani al-Mulk and the textual content of the One Thousand and One Nights book. The author's perspective in selecting samples has a significant impact. The selection criterion is the compatibility of the work with the components of the losing theory, and 5 illustrations are examined. The exploration of Iranian painting commenced in the early 20th century and has witnessed substantial growth in the past few decades. Given the significant impact of the One Thousand and One Nights across diverse global literary and cultural domains, delving into the illustrations of this ancient literary masterpiece appears imperative. Discussion The largest illustrated cultural book in Iran, One Thousand and One Nights, with over three thousand sessions, was created in the 13th century while preserving traditional cultural values. The Iranian painter connects humans with their environment and highlights the details of everyday life. Ultimately, the human figure emerges and takes center stage. Sani al-Mulk, in his creations, expresses a comprehensive image of a new culture, emphasizing individual values and human greatness while adopting a somewhat innovative approach. He relies on his inherent creativity and, through aesthetic efforts, presents scenes and familiar spaces that are recognizable and even introduces contemporary living characters instead of historical ones, adding allure to his work.One Thousand and One Nights, while retelling mythical tales and fantasies, portrays scenes of life such as streets and markets that reflect reality. The visual elements are drawn in accordance with the narrative of the story and a realistic perspective. Sani al-Mulk, understanding the principles of European naturalism, attempts to achieve a fresh synthesis of European and Iranian visual traditions. His intentional deviation from precise perspective rules, reflective of his inclination towards the traditions of Iranian art, allows him to break free from deep realism and preserve two-dimensional design and coloring.These characteristics are evident in the storytelling and visual representation of the story of the Ebony Horse. The Ebony Horse recounts the story of a king and his son, Hormoz, whose fate is transformed by receiving a miraculous gift. Iranian literature and arts have continuously integrated ancient patterns to describe a universal world passed down from their ancestors.Another important theme is Mikhail Bakhtin's theory of literature in the 20th century, which explores various human activities and the role of speech, understanding dialogical aspects, evaluation, and responsiveness. Art also evolves in line with his thought, showing a certain resemblance between them. Bakhtin sees discourse in the realm of social order, believing that society begins with the emergence of the second person. Language fundamentally possesses a qualitative socio-mental aspect, and its existence is of fundamental importance to humans. Human existence is found in connection with other living entities, and the fundamental reality of human existence is found in the bond between individuals.In this study, the story of the Ebony Horse is briefly mentioned, and then the narrative and visual representation of Sani al-Mulk are analyzed based on Bakhtin's theories. The narrative and forthcoming works are examined and analyzed in terms of concepts such as polyphony, chronotope, otherness, and carnivalesque, which are innovations in the present text. Conclusion The research results indicate that narrative expression, dialogical principle, polyphony, chronotope, and carnivalesque elements are identifiable in the content of the Ebony Horse story. Sani al-Mulk adeptly captured these elements in his illustrations. Indeed, there exists an evolutionary connection between the text and the visual portrayal of the linear rendition of the Ebony Horse story. This connection ensures that the identical principles of conversational logic, identifiable in the text, are prominently showcased in the illustrations.